Influence of uron resins on the performance of UF resins as adhesives for plywood - Wei Gao; Jianzhang Li (Maderas: Ciencia y Tecnología, 2012)
Uron resin, a kind of urea-formaldehyde (UF) resin containing much more uron structure, were prepared. Several modified UF resins were obtained from mixing uron resins with normal UF resins as well as synthesizing UF resin with uron resin as raw material. This work demonstrated that the introducing of the uron structure reduced free formaldehyde content of UF resin and formaldehyde emission levels in bonded plywood panels significantly, the former were reduced by 76% and 84% in the latter. The synthesis time of uron resin can be shortened to 8 hours. The test result of free formaldehyde content, formaldehyde emission levels and bond strength indicated that specimen of 20 parts uron resin synthesized in 8 hours mixed with 100 parts UF resins (F/U molar ratio of 1.3) had a potential advantage to industrial application. The beneficial effect of uron resin on the performance of UF resin can be attributed to the opening of uron cycle structure and the following reaction with free formaldehyde and its oligomeric glycol forms.